The Relevance of the Thoughts of the Winners of The "Puteri Kartini Jawa Timur" Event With Kartini's Thoughts on Gender Equality and Nationalism - Izzah, Aqidatul; Suhartono, Edi; Al Atok, A. Rosyid (ARISTO, 2025)
This research is motivated by the relevance of R.A. Kartini's thoughts on gender equality and nationalism with the thoughts of the winners of the "Puteri Kartini Jawa Timur Event." The objectives of the research include a description of Kartini's thoughts and the winners in 2024 of the event and an analysis of their relevance. The research method uses a qualitative approach with a descriptive type through in-depth interviews and literature studies. The results of the study show the application of gender equality values through emancipation, education, and criticism of traditions such as seclusion and polygamy. Humanist nationalism is also manifested in the preservation of local culture through educational programs and social campaigns. The conclusion of this study reveals that the "Puteri Kartini Jawa Timur Event" is a platform for advocacy of gender equality and nationalism while promoting Kartini's values that are relevant in building a strong and progressive national identity.